Avaliação radiográfica do comportamento ósseo cervical nos implantes com hexágono externo reabilitados pelo conceito da platform switching e submetidos à carga imediata com próteses fixas parafusadas provisórias - Peredo-Paz, Luis Guillermo (2011)
In the present study, the main purpose was to evaluate radiographically during six and twelve months after implants installation the cervical bone around external hexed implants with expanded platform (XP 5.0 mm) and regular platform (ST 4.1 mm) using 4.1 mm diameter abutments for both implants system and supporting a full fixed temporary acrylic bridge submitted to immediate loading. Nine maxillary edentulous patients were treated in this study and each one received six external hexed implants, three of these implants were 5 mm diameter expanded cervical platform (XP, Biomet 3i, USA) and the other three implants were regular diameter cervical platform (ST 4.1 mm, Biomet 3i, Brazil). All installed implants received standard diameter components (4.1 mm Biomet 3i), characterizing the platformswitching concept on the XP implants. The implants installation was performed in an alternating fashion. The installation process always was initiated from the right side of the mouth with one type of implant; the next implant had a different diameter at the cervical part. It all finalized with the installation of six implants on the left side of the maxilla. All cases were treated in a single surgical procedure to reduce trauma, using less drilling sequence to increasing the initial implant stability and the prosthetic components were installed during surgery to perform the ISQ analisys with the Osstell Mentor system. Final impression was taken for the fabrication of the fixed screw retained acrylic bridges, using the provisional metal sleeves for micro-unit abutments and delivered to the patients within 24 hours after surgery. At the placement of the restorations, 6 and 12 months later (named Time 0 = T0, Time 6 = T6 and Time 12 = T12) radiographs were performed using the conventional parallel cone technique to observe the cervical bone behavior during these three periods. These x-rays were digitalized and measured with the Radio Cef/Radio Imp software. Also the ISQ of all implants was messure at abutment connection during surgery or Period 0 = P0, six and 12 months later (P 6 and P12, respectively). From the 54 implants placed, only one failed during the first control time, six months later. Peri implant cervical bone loss was found for both types of implants. The ST implants showed an average bone loss of 1.61 and 1.99 mm in the vertical direction and 1. 07 and 1.35 mm in the horizontal direction, during 6 and 12 months of control. For the XP type of implants, we found 1.21 and 1.76mm for the vertical direction messurements and 0.89 and 0.96 mm for the horizontal direction of bone loss during the same periods of observation. Within the limits of this study, both implants had good clinical result, but the XP implants rehabilitated under the platform switching protocol, showing less bone loss in vertical and horizontal components.